Technological Innovation and Market Governance forTrader Satisfaction in Traditional Markets: Evidence fromGarut Regency - INTAN ALYA KHOERUNNISA; DINI TURIPANAM ALAMANDA; DWI NURHAYATI (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2025)
Abstract. Traditional markets in non-metropolitan regions need to adapt to changing service expectations, retail competition, and digital transaction practices. However, previous studies have often examined market revitalization, service quality, digital payment adoption, or governance separately, while limited attention has been given to how these factors explain trader satisfaction as an evaluation of market management practices. This study examines the influence of infrastructure quality, service quality, government support, technological innovation, and market governance on trader satisfaction in traditional markets in Garut Regency. Market governance is defined in this study as the clarity of rules, fair treatment, transparency, complaint mechanisms, and communication between traders and market managers. Data were collected from 100 active traders using purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3. The results show that infrastructure quality, service quality, technological innovation, and market governance significantly influence trader satisfaction, while government support does not show a significant effect. Market governance has the strongest effect, and the model explains 64.4% of the variance in trader satisfaction. These findings provide empirical insight that trader satisfaction is shaped by the alignment of physical facilities, service delivery, technological practices, and governance mechanisms. Practically, local governments and market managers should translate support programs into concrete improvements that traders can directly experience. Keywords: Infrastructure quality, market governance, service quality, technological innovation, trader satisfaction